2010
DOI: 10.1142/s1230161210000126
|View full text |Cite
|
Sign up to set email alerts
|

Justifying Additive Noise Model-Based Causal Discovery via Algorithmic Information Theory

Abstract: A recent method for causal discovery is in many cases able to infer whether X causes Y or Y causes X for just two observed variables X and Y. It is based on the observation that there exist (non-Gaussian) joint distributions P(X,Y) for which Y may be written as a function of X up to an additive noise term that is independent of X and no such model exists from Y to X. Whenever this is the case, one prefers the causal model X → Y. Here we justify this method by showing that the causal hypothesis Y → X is unlikel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Janzing & Steudel (2009) give further theoretical support for this principle using the concept of Kolmogorov complexity and Peters et al (2009) use this way of reasoning for detecting the arrow of time.…”
Section: Additive Noise Models For Discrete Variablesmentioning
confidence: 94%
“…Janzing & Steudel (2009) give further theoretical support for this principle using the concept of Kolmogorov complexity and Peters et al (2009) use this way of reasoning for detecting the arrow of time.…”
Section: Additive Noise Models For Discrete Variablesmentioning
confidence: 94%
“…The second definition of γ, on the other hand, gets a particularly simple meaning when (11) in Postulate 1 holds. Then…”
Section: Strength Of Confoundingmentioning
confidence: 99%
“…We store the best split per attribute (lines 10-12). Then we greedily select the overall best split and iterate until no further split can be found that can save any bits (lines [13][14][15][16]. We refer the interested reader to the original paper [36] for more details on Pack.…”
Section: Algorithm 1: Greedypackmentioning
confidence: 99%
“…The algorithmic information theoretic viewpoint of causality is more general in the sense that any physical process can be simulated by a Turing machine. Janzing and Steudel [13] use it to justify the ANM-based causal discovery.…”
Section: Related Workmentioning
confidence: 99%